The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12913-022-08801-w
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the ‘Grip on Health’ intervention in general and occupational health practice

Abstract: Background For working patients with a lower socioeconomic position, health complaints often result from a combination of problems on multiple life domains. To prevent long-term health complaints and absence from work, it is crucial for general and occupational health professionals to adopt a broad perspective on health and to collaborate when necessary. This study aimed to evaluate how the ‘Grip on Health’ intervention is implemented in general and occupational health practice to address multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 44 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…OHPs may hold different views on the intervention than lower SEP workers themselves, 34 affecting the credibility and transferability of findings 33 . However, the contextual factors affecting the implementation of Grip on Health in this study were also found in other studies, 9,22 suggesting good transferability and confirmability of findings. Another limitation is that selection bias may have occurred.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…OHPs may hold different views on the intervention than lower SEP workers themselves, 34 affecting the credibility and transferability of findings 33 . However, the contextual factors affecting the implementation of Grip on Health in this study were also found in other studies, 9,22 suggesting good transferability and confirmability of findings. Another limitation is that selection bias may have occurred.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, OHPs who succeeded to deliver the intervention could not always deliver all intended steps because of the online consultation sessions. In line with this, another study evaluating Grip on Health among OHPs and general practitioners showed that it was not feasible to use the materials in an online meeting 22 . Furthermore, during the COVID-19 pandemic, stakeholders at the workplace may have had other priorities than to support preventive interventions focused on multiple life domains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations